First experimental characterization of CaCl2 coated heat exchanger for thermochemical heat transformer applications in industrial waste heat recovery. (5th June 2023) - Michel, Benoit; Dufour, Nicolas; Börtlein, Clémentine; Zoude, Camille; Prud'homme, Elodie; Gremillard, Laurent; Clausse, Marc
Highlights: CaCl2 equilibrium were identified for thermochemical heat transformer application. 2 salt implementations were tested in realistic operating conditions. Specific power up to 341 W/kg for a temperature lift of 60 K has been obtained. Abstract: This study aims at evaluating the performance of a heat exchanger coated with CaCl2 (PVA polyvinyl alcohol used as binder) for Thermochemical Heat Transformers (THT) applications in industrial waste heat recovery. For this purpose, an experimental test bench has been built allowing to test operating temperatures up to 160 °C. A model heat exchanger plate is used to test two configurations: a thick layer of CaCl2 to model a packed bed reactor (used as reference) and a CaCl2 -PVA deposit to model a coated reactor. For the packed bed configuration, results comparable to that of the literature are obtained with a specific power of 180 W/kg obtained for a temperature lift of 60 K. A high sensitivity to temperature lift is identified with a decrease of the specific power down to 38 W/kg for a lift of 77 K. The coated heat exchanger configuration achieves significantly higher performance with a specific power up to 341 W/kg for a temperature lift of 63 K. However, the analysis of the repeatability tests highlights a rapid change in temperature profiles highlighting a change in properties of the CaCl2 /PVA compound material. Next steps will consist in enhanced material formulation and change in deposit protocol and to move to work at small reactor scale to assess system performance.